Active strike-slip faulting in the Zagros Mountains: Geological and geomorphological evidence of the pull-apart Zaribar Lake basin, Zagros, NW Iran. (1st May 2019) - Rahimzadeh, Bahman; Bahrami, Shahram; Mohajjel, Mohammad; Mahmoudi, Hossein; Haj-Azizi, Farzad
Highlights: The Zeribar Lake basin is a pull-apart basin along the MRF in the Zagros Mountains. This pull-apart basin is related to a dextral major strike-slip fault, MRF, in the region. Numerous normal faults and grabens are evidence of extensional deformation. The strike-slip faults form some characteristic landforms. Abstract: The Zaribar Lake is situated along the Main Recent Fault, a dextral major strike-slip active fault system in the Zagros collision zone. The formation of the Zaribar Lake in Late Pleistocene is associated with the activities of the Main Zagros Reverse Fault, initiated in Late Oligocene, and with the Main Recent Fault, whose inception occurred about 5 Ma ago. Metamorphic, intrusive and ophiolitic rocks in the Zagros suture zone are affected by a normal fault system in the Zaribar area. Geometry and kinematics of these normal faults indicate that the Zaribar Lake is generated in a releasing zone. The strike of the Main Recent Fault varies from 300° to 330° along the Marivan fault segment. The releasing bend of the Marivan Fault around the Zaribar Lake has resulted in the extensional deformation by which the lake has been downdropped between two strike-slip faults. Besides the extensional mechanism of the main right-lateral strike-slip faults that has resulted in the formation of the Zaribar as a large-scale pull-apart basin, minor strike-slip faults have also produced specific landforms around the lake. Small-scale normal faults and large scale grabens developed around the lake are geological indicators of extensional areas. Geomorphological evidence also support the pull-apart origin for the Zaribar Lake. Beheaded rivers, numerous offsets in drainage system, half-broom shaped drainage pattern, sag ponds with different scales, linear and strike-parallel valleys and alluvial fan with high sweep angle and width/length ratio confirm the movements along right-lateral, strike slip faults around the Zaribar.